2011
DOI: 10.3171/2011.9.focus11205
|View full text |Cite
|
Sign up to set email alerts
|

Incidental findings on cranial imaging in nonagenarians

Abstract: Object The aim of this article was to report on the nature and prevalence of incidental imaging findings in a consecutive series of patients older than 90 years of age who underwent intracranial imaging for any reason. Methods The authors retrospectively reviewed the electronic medical and imaging records of consecutive patients who underwent brain MR imaging at a single institution over a 153-month inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…While MRI scans typically take a longer time than CT scans, a study using satisfaction questionnaires indicated that MRI sessions of up to an hour were feasible in this age group, where the oldest-old participants (90-93 years, N = 13) tolerated the procedures as well as younger-old participants (72-80 years, N = 16) with no statistically significant differences in satisfaction surveys between the groups [18]. One study retrospectively assessed clinical MRI scans of patients between 90 and 100 years of age for incidental findings, and reported that out of 177 patients, the most common findings were acute ischemic changes or cerebrovascular accident (20%), intracranial tumors (8%), and intracranial aneurysms (3%) [19].…”
Section: The Advent Of Mri: Structural Studies Using Anatomical Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…While MRI scans typically take a longer time than CT scans, a study using satisfaction questionnaires indicated that MRI sessions of up to an hour were feasible in this age group, where the oldest-old participants (90-93 years, N = 13) tolerated the procedures as well as younger-old participants (72-80 years, N = 16) with no statistically significant differences in satisfaction surveys between the groups [18]. One study retrospectively assessed clinical MRI scans of patients between 90 and 100 years of age for incidental findings, and reported that out of 177 patients, the most common findings were acute ischemic changes or cerebrovascular accident (20%), intracranial tumors (8%), and intracranial aneurysms (3%) [19].…”
Section: The Advent Of Mri: Structural Studies Using Anatomical Mrimentioning
confidence: 99%
“…• Some common incidental findings found on the MRI scans of the oldest-old include ischemic changes, intracranial tumors, and intracranial aneurysms [19]. Individuals without dementia who experienced hallucinations or delusions were more often found to have calcification of the basal [13]…”
Section: Studiesmentioning
confidence: 99%
“…Structural magnetic resonance imaging (MRI), widely used in research studies of community based cohorts, can reveal incidental findings in asymptomatic individuals. Previous studies have demonstrated that incidental brain findings are commonly detected in healthy pediatric (Gur et al 2013), general adult (Håberg et al 2016;Vernooij et al 2007) and older community-dwelling subjects (Sandeman et al 2013;Al-Holou et al 2011). In an international systematic review of 19,559 adults who underwent a brain MRI for occupational, clinical or commercial screening, the crude prevalence of incidental findings was 2.7% (Morris et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, elderly people have a predisposition for various diseases including brain tumor and brain infarction compared with younger people, and the imaging examinations sometimes detect brain diseases incidentally. 14,15 However, only a small number of reports have so far evaluated the efficacy of these imaging tests in diagnosing patients who report orofacial pain and paresthesia. The aim of this study was to compare the efficacy of CT and MRI examinations in diagnosing orofacial pain and paresthesia.…”
mentioning
confidence: 99%